Interaction Mindsets, Interactional Behaviors, and L2 Development: An Affective‐Social‐Cognitive Model. Issue 2 (10th November 2016) - Sato, Masatoshi
Abstract: This classroom‐based study explored links among second language (L2) learners' interaction mindsets, interactional behaviors, and L2 development in the context of peer interaction. While peer interaction research has revealed that certain interactional behaviors (e.g., receiving corrective feedback and engaging in collaborative interaction) assist L2 learning, it is yet unknown why some learners exhibit these interactional behaviors or how learners' affective states impact their L2 development. The participants were two Grade 10 English as a foreign language classes in Chile ( N = 53). Three data sets were collected: (a) interaction mindset data based on pretask interviews with focus groups from each class ( n = 10); (b) interaction data pertaining to the communicative tasks of the focus groups; and (c) L2 development data from both classes consisting of oral and written production tests focusing on grammar and lexis. Results indicated that L2 development was mediated by learners' interaction mindsets, which in turn affected their interactional behaviors. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible in the IRIS digital repository athttp://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .